Pengaruh Komunikasi, Disiplin Kerja, Dan Motivasi Kerja Terhadap Kepuasan Mahasiswa Dengan Kualitas Pelayanan Sebagai Variabel Intervening - Eva Suryani; Mandra Adrika Putra; Tri Yanti; O.P. Bismark (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of communication, work discipline, and work motivation on student satisfaction with service quality as an intervening variable at the STKIP Widyaswara Indonesia Secretariat. The study was conducted on 100 active students who had used secretariat services, using a purposive sampling technique. Data were collected through observation, documentation studies, and questionnaires, then analyzed using the PLS-based SEM method with the help of SmartPLS 3. The results showed that communication and work discipline did not significantly influence student satisfaction or service quality. In contrast, work motivation had a positive and significant effect on student satisfaction and service quality. In addition, service quality was proven to have a significant effect on student satisfaction. These findings are expected to be the basis for strategic recommendations in improving service quality at the STKIP Widyaswara Indonesia Secretariat.